Risk factors for dermatological complications of anti-TNF therapy in a cohort of children with Crohn's disease - Hradsky, Ondrej; Kazeka, Denis; Copova, Ivana; Lerchova, Tereza; Mitrova, Katarina; Pospisilova, Kristyna; Sulovcova, Miroslava; Zarubova, Kristyna; Bronsky, Jiri (European journal of pediatrics, 2021)
Studies showing a substantial frequency of dermatologic complications in paediatric Crohn's disease (CD) patients on anti-tumour necrosis factor (TNF) therapy preferentially include patients treated with infliximab. We aimed to identify risk factors for the cumulative incidence of skin complications in a paediatric cohort receiving either adalimumab or infliximab and found an association between current skin complications and the patient's current clinical condition. This study retrospectively evaluated dermatologic complications in an inception cohort of 100 paediatric CD patients receiving the first anti-TNF (Motol PIBD cohort). Patient data were collected every 3 months. The lesions were classified as psoriatic, atopic dermatitis, or others. We used Cox regression to evaluate the association between predefined variables and the time to complication and a generalised linear mixed model to assess the association between the patient's current condition and the occurrence of complications. Among the 89 included children, 35 (39%) presented with dermatologic lesions. The only predictor associated with any complication was infliximab (versus adalimumab) therapy (hazard ratio [HR]: 2.07; 95% confidence interval [CI]: 1.03-4.17; p = 0.04). Infliximab therapy (HR: 5.5; 95%CI: 1.59-19.06; p = 0.01) and a family history of atopy (HR: 3.4; 95%CI 1.35-8.57, p = 0.002) were associated with early manifestation of atopic dermatitis. Lower C-reactive protein levels (odds ratio [OR], 0.947; 95% CI, - 0.898 to 0.998; p = 0.046) and infliximab (versus adalimumab) were associated with the occurrence of any dermatologic complications (OR, 5.93; 95% CI, 1.59-22.07; p = 0.008).Conclusion: The frequency of skin complications seems high in paediatric CD patients treated with anti-TNF and is even higher in those treated with infliximab. What is Known: •The dermatologic complications occur during treatment with anti-tumour necrosis factor. •The frequency of skin complications in paediatric patients with Crohn's disease is high. What is New: •Infliximab (vs. adalimumab) was identified as a strong risk factor for the cumulative incidence of skin complications. •Lower C-reactive protein levels were associated with the current occurrence of dermatologic complications.
Keywords: Skin complications; Retrospective Studies; výsledek terapie; Tumor Necrosis Factor-alpha; Adalimumab; infliximab; Crohnova nemoc; Psoriasis; Infliximab; dítě; Child; TNF-alfa; Eczema; retrospektivní studie; Humans; inhibitory TNF; Crohn Disease; Tumor Necrosis Factor Inhibitors; rizikové faktory; Risk Factors; Treatment Outcome; lidé